Propriedades elétricas e estruturais do niobato de potássio e estrôncio obtido pelo método de Pechini - Lima, Alan Rogério Ferreira (Universidade Federal de São Carlos, 2015)
The search for new technologies more efficient and environmentally sustainable, triggered the search for new materials and synthesis routes that present a low economic and energy impact. In this context, potassium and strontium niobate (KSr2Nb5O15) tetragonal tungsten bronze structure (type-TTB) was doped with La+3 and Ti+4 ions, with the aim of improving the structural and electrical properties and understand the structural effects on the dielectric properties of the structure host. Ceramics with stoichiometry KSr2Nb5O15 and K1+xSr2- 2xLaxNb5O15, K1+4xSr2-1.5xTixNb5-xO15 and K1+2xSr2-2xLaxNb5-xTixO15 (x = 0.05; 0.10 e 0.15) were synthesized using the Pechini method maintaining a molar ratio of citric acid:metal 4:1, mass ratio citric acid:ethylene glycol 60:40. The parameters of time and calcining temperature were optimized in order to obtain powders with high crystal domain crystallographic coherency. The powders were uniaxially and isostatically pressed and sintered in order to obtain dense ceramic bodies for electrical measurements. The ceramic bodies were characterized by morphological, structural and electrical analysis. The presence of La+3 and Ti+4 ions in octahedral led to changes in the network, and morphology of the host structure resulting in different dielectric behavior. The higher dielectric constant value was observed for the host structure KSr2Nb5O15. The dielectric behavior observed for solid solutions K1+xSr2-2xLaxNb5O15, K1+4xSr2-1.5xTixNb5-xO15 and K1+2xSr2-2xLaxNb5-xTixO15 (x = 0.05; 0.10 e 0.15) was attributed to growth abnormal grain in the ceramic body, structural modulations, occupation of octahedral sites and distortions of the octahedral host structure.
Electrical properties and structural potassium and strontium niobate obtained by Pechini method
Keywords: Físico-química; Propriedades elétricas; Cerâmica eletrônica; Novas tecnologias; CIENCIAS EXATAS E DA TERRA::QUIMICA; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::DETERMINACAO DE ESTRUTURA DE COMPOSTOS INORGANICOS